Morphometric Analysis of the Middle Meningeal Artery Organization in Humans—Embryological Considerations - Harthmann da Silva, Tales; Ellwanger, Joel Henrique; Silva, Helen Tais da Rosa; Moraes, Daniela; Dotto, Anderson Cesar; Viera, Vinicius de Aguiar; de Campos, Deivis (Journal of Neurological Surgery Part B: Skull Base, 2013)
The middle meningeal artery (MMA) is the largest branch of the internal maxillary artery supplying the meninges. The complex sequence of MMA development gives many opportunities for variant anatomy. Additionally, the variations in the origin of the MMA are of clinical importance when dealing with fractures of the base of the skull, epidural hematomas, and bypass procedures. Therefore, various anastomosis and aberrant origins of the MMA have been documented in literature. However, there are no reports about some morphometric aspects of this important arterial segment. Thus, in this study, we decided to investigate the anatomical organization of the MMA through the bony groove measurements from human skulls (n = 50 subjects). Six measurements were performed bilaterally: angle of the main trunk, length of the main trunk, angle between the frontal and parietal branches, length of the frontal branch, length of the parietal branch, and length of the bony tunnel formed by the frontal branch. We showed that the anatomical organization of the MMA is bilaterally similar, except for the length of the parietal branch (p = 0.009). Moreover, our results provide baseline normal values for future studies aimed at further elucidating the functional and morphological pattern of the MMA.
Keywords: anatomy; bony groove; anatomical variation; middle meningeal artery